Structural relationship of goal content, behavioural regulation, and coping self-efficacy on amount of physical activity among undergraduate students in Health Campus, Universiti Sains Malaysia - Shirlie, Chai (2018)
Introduction: Physical activity engagement can be influenced by complex interaction between psychological, social, environmental and biological influences. Therefore, there is a need for scientific understanding of motivation and behaviour manifestation, in the context of doing of physical activities. Yet, there is lack of evidence on validated instrument for the measurement of the psychological factors, namely goal content, behavioural regulation, and coping self-efficacy in the Malaysian context. The effect of their relationships with the amount of physical activity remains unclear. Objective: This study aimed to determine measurement validity of the Malay-translated version questionnaires assessing goal content, behavioural regulation, and coping self-efficacy. Subsequently, examine their structural relationships with amount of physical activity among undergraduate students in Health Campus, Universiti Sains Malaysia (USM). Method: A cross-sectional study using questionnaire approach was conducted among undergraduate students in Health Campus, USM. Participant was selected using convenience sampling, a non-probability sampling method. Goal content, behavioural regulation, and coping self-efficacy were measured using Malay-translated version of Goal Content for Exercise Questionnaire (GCEQ), Behavioural Regulation in Exercise Questionnaire-3, and Coping Self-Efficacy Scale (CSE). Descriptive statistics, confirmatory factor analysis (CFA), and structural equation modelling (SEM) were conducted for statistical analyses.Results: A total of 674 students participated in this study. In measurement model assessment, the Malay version of GCEQ indicated that the 20-item model was fit with all items remained: CFI = 0.929; SRMR = 0.052; RMSEA = 0.061 (90% CI: 0.056, 0.067), probability RMSEA = 0.001. The Malay version of BREQ-3 displayed good fit after removing Identified Regulation subscale: CFI = 0.949; TLI = 0.938; SRMR = 0.052; RMSEA = 0.049 (90% CI: 0.043, 0.055), probability RMSEA = 0.614. Meanwhile, 16-item Malay version of CSE showed an excellent model fit: CFI = 0.955; TLI = 0.947; SRMR = 0.037; RMSEA = 0.046 (90% CI: 0.039, 0.054), probability RMSEA = 0.779. The composite reliability for Malay version of GCEQ, BREQ-3, and CSE ranged from 0.777 - 0.851, 0.746 - 0.841, and 0.804 - 0.883 respectively. In addition, the SEM model showed an excellent fit: CFI = 0.980; TLI = 0.947; SRMR = 0.052; RMSEA = 0.055 (90% CI: 0.041, 0.069), probability RMSEA = 0.275 with 23 hypotheses supported. Several indirect relationships were observed involving pathways from coping self-efficacy to physical activity through components of goal content and behavioural regulation. Conclusion: The hypothesised structural model tested in current study provided evidences of the direct and indirect relationships among goal content, behavioural regulation, coping self-efficacy, and amount of physical activity. The findings provide valuable information that could help the individuals, health policy makers, and health educators in enhancing the performance and participation in physical activity among university students.